The need to equipped academy libraries in some tertiary institution/college of education - Muokwelu, Maureen Ifeyinwa (Humanities Horizon, 2025)
Academic libraries are essential components of tertiary institutions and Colleges of Education, serving as the backbone of teaching, learning, and research. This study examines the urgent need to equip academic libraries in some Nigerian tertiary institutions, focusing on their role in enhancing student learning outcomes, supporting academic staff, and promoting digital literacy. This study used a systematic review design to examine literature published between 2020 and 2025. Relevant peer-reviewed articles, reports, and grey literature were sourced from databases such as Google Scholar, JSTOR, ERIC, ResearchGate, and AJOL, using specific keywords. After screening for relevance and quality, eligible studies were reviewed by two independent evaluators. Results reveal persistent challenges, including inadequate funding, outdated resources, insufficient digital infrastructure, and a shortage of trained personnel. These deficiencies significantly hinder the effectiveness of academic libraries and compromise educational quality. The study further explores the implications of these challenges and highlights the necessity for government and institutional support, public-private partnerships, digital library initiatives, and continuous capacity building for library staff. It concludes that equipping academic libraries is not only a strategic investment in higher education but also a critical step toward achieving sustainable development and global competitiveness. The study recommends robust policy interventions and multi-stakeholder collaboration to reposition academic libraries as modern, resource-rich learning environments capable of meeting 21st-century academic demands.